Myocarditis in Relation to Angiographic Findings in Patients With Provisional Diagnoses of MINOCA - Hausvater, Anaïs; Smilowitz, Nathaniel R; Li, Boyangzi; Redel-Traub, Gabriel; Quien, Mary; Qian, Yingzhi; Zhong, Judy; Nicholson, Joseph M; Camastra, Giovanni; Bière, Loïc; Panovský, Roman; Sá, Montenegro; et al. (JACC. Cardiovascular imaging, 2020)
OBJECTIVES: The aim of this study was to determine the prevalence of myocarditis among patients presenting with myocardial infarction with nonobstructive coronary arteries (MINOCA) in relation to the angiographic severity of nonobstructive coronary artery disease (CAD). BACKGROUND: MINOCA represents about 6% of all cases of acute myocardial infarction. Myocarditis is a diagnosis that may be identified by cardiac magnetic resonance (CMR) imaging in patients with a provisional diagnosis of MINOCA. METHODS: A systematic review was performed to identify studies reporting the results of CMR findings in MINOCA patients with nonobstructive CAD or normal coronary arteries. Study-level and individual patient data meta-analyses were performed using fixed- and random-effects methods. RESULTS: Twenty-seven papers were included, with 2,921 patients with MINOCA; CMR findings were reported in 2,866 (98.1%). Myocarditis prevalence was 34.5% (95% confidence interval [CI]: 27.2% to 42.2%) overall and was numerically higher in studies that defined MINOCA as myocardial infarction with angiographically normal coronary arteries compared with a definition that permitted nonobstructive CAD (45.9% vs. 32.3%; p = 0.16). In a meta-analysis of individual patient data from 9 of the 27 studies, the pooled prevalence of CMR-confirmed myocarditis was greater in patients with angiographically normal coronary arteries than in those with nonobstructive CAD (51% [95% CI: 47% to 56%] vs. 23% [95% CI: 18% to 27%]; p < 0.001). Men and younger patients with MINOCA were more likely to have myocarditis. Angiographically normal coronary arteries were associated with increased odds of myocarditis after adjustment for age and sex (adjusted odds ratio: 2.30; 95% CI: 1.12 to 4.71; p = 0.023). CONCLUSIONS: Patients with a provisional diagnosis of MINOCA are more likely to have CMR findings consistent with myocarditis if they have angiographically normal coronary arteries.
Keywords: Female; Coronary Vessels; Coronary Angiography; ženské pohlaví; myokarditida; Predictive Value of Tests; prediktivní hodnota testů; lidé; koronární angiografie; koronární cévy; Risk Factors; nemoci koronárních tepen; Male; Coronary Artery Disease; rizikové faktory; Myocardial Infarction; Myocarditis; mužské pohlaví; infarkt myokardu; Humans